2018
DOI: 10.1016/j.molcel.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

ZUFSP Deubiquitylates K63-Linked Polyubiquitin Chains to Promote Genome Stability

Abstract: Deubiquitylating enzymes (DUBs) enhance the dynamics of the versatile ubiquitin (Ub) code by reversing and regulating cellular ubiquitylation processes at multiple levels. Here we discovered that the uncharacterized human protein ZUFSP (zinc finger with UFM1-specific peptidase domain protein/C6orf113/ZUP1), which has been annotated as a potentially inactive UFM1 protease, and its fission yeast homolog Mug105 define a previously unrecognized class of evolutionarily conserved cysteine protease DUBs. Human ZUFSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 54 publications
1
66
0
Order By: Relevance
“…It co-localizes with RPA-ssDNA at micro-irradiation stripes and at FokI-induced DSBs and its recruitment is mediated by ubiquitin-binding domains and a series of zinc fingers at its N-terminus. KD of UBC13 strongly decreases ZUFSP accumulation at damage sites further supporting the role of K63-linked ubiquitin chains in this process [ 290 ]. An interaction with RPA was also reported by all three studies but RPA depletion did not impair the recruitment of ZUFSP to damage sites [ 96 , 290 , 291 ].…”
Section: De-ubiquitylation and Replication Stressmentioning
confidence: 92%
See 1 more Smart Citation
“…It co-localizes with RPA-ssDNA at micro-irradiation stripes and at FokI-induced DSBs and its recruitment is mediated by ubiquitin-binding domains and a series of zinc fingers at its N-terminus. KD of UBC13 strongly decreases ZUFSP accumulation at damage sites further supporting the role of K63-linked ubiquitin chains in this process [ 290 ]. An interaction with RPA was also reported by all three studies but RPA depletion did not impair the recruitment of ZUFSP to damage sites [ 96 , 290 , 291 ].…”
Section: De-ubiquitylation and Replication Stressmentioning
confidence: 92%
“…More recently, a novel class of DUB was identified and shown to play a role in the RSR. Three groups simultaneously identified ZUFSP (zinc finger with UFM1-specific peptidase domain protein) as a DUB with a high preference for long K63-linked ubiquitin chains [ 290 , 291 , 292 ]. ZUFSP interacts with and cleaves K63-linked chains via tandem ubiquitin-binding domains and a c-terminal C78 papain-like peptidase domain.…”
Section: De-ubiquitylation and Replication Stressmentioning
confidence: 99%
“…The human proteome contains ∼100 DUBs belonging to two distinct enzyme classes: the cysteine proteases and the metalloproteases. The cysteine protease class comprises six different enzyme families: ubiquitin-specific proteases (USPs), ubiquitin carboxyl-terminal hydrolases (UCHs), ovarian tumor proteases (OTUs), Machado-Joseph ( Josephin) domain-containing proteases (MJDs), motif interacting with Ub-containing novel DUB family (MINDY) [85], and zinc finger containing ubiquitin peptidase 1 (ZUFSP/ZUP1) [86][87][88][89]. The metalloprotease enzyme class consists of a single family of enzymes: JAB1/MPN/MOV34 ( JAMMs).…”
Section: Targeting Deubiquitinationmentioning
confidence: 99%
“…Josephin domain DUBs], one is the motif interacting with ubiquitin (MIU)-containing novel DUB family [MINDYs], one consists of the JAMM/MPN+ family of metalloproteases, and the seventh is represented by the recently identified ZUFSP (Haahr et al, 2018;Kwasna et al, 2018;Mevissen and Komander, 2017). By a mouse genetic approach our laboratory reported that loss of the ubiquitin-specific protease 3 (USP3) protects the HSCs from functional decline through modulation of ubiquitin-dependent DNA damage response (DDR), a critical genome maintenance pathway (Lancini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%